ПЕДАГОГИЧЕСКИЕ ПРИНЦИПЫ СОВЕРШЕНСТВОВАНИЯ УРОКОВ ФИЗИЧЕСКОГО ВОСПИТАНИЯ ДЛЯ УЧАЩИХСЯ НАЧАЛЬНЫХ КЛАССОВ - Абдукаримов, Н.А. (SCIENCE and SOCIETY, 2025)
This article is aimed at serving as a pedagogical basis for the quality and effective organization of physical education classes in primary education in the education system of the Republic of Uzbekistan.
Keywords: physical culture; sports; lessons; education; science; competence; science education; school